Smoking, Muslim religious commitments, and the experience and behaviour of Ramadan in Pakistani men - Khan, Ziasma Haneef (Mental health, religion & culture, 2013)
This study examined the possibility that smoking may interfere with Muslim commitments in general and with the experience and behaviour of Ramadan in particular. During Ramadan, a sample of 29 smoking and 46 non-smoking Pakistani men responded to measures of smoking, Religious Orientation, Religious Interest, Positive and Negative Ramadan Experience, and Ramadan Behaviour. Various indices of smoking predicted a disinterest in religion, less of an Intrinsic Religious Orientation, lower levels of Positive Ramadan Experience, higher Negative Ramadan Experience, and reductions in Ramadan Behaviour. These data offered preliminary support for the suggestion that smoking presents a challenge to Muslim beliefs and practices, especially during Ramadan.